Gestational Diabetes and Risk of Developing Postpartum Type 2 Diabetes: How to Improve Follow-up? - El Ouahabi, Hanan (Int J Prev Med, 2019)
BACKGROUND: Gestational diabetes mellitus (GDM) is defined by World Health Organization as glucose intolerance diagnosed for the first time during pregnancy; GDM affects 7% of pregnancies. Women with earlier GDM have higher risk to develop type 2 diabetes (T2D). The aim of our study was to evaluate the outcomes of GDM and to assess the impact of recalling patients in the postpartum stage by phone, the target was to assess T2D or impaired glucose tolerance in women with a history of GDM. METHODS: This prospective study included 200 patients with GDM that have received education sessions regarding the major interest of screen T2D using 75 g of oral glucose tolerance testing in the 3(rd) month after birth. RESULTS: Only 22.5% (n = 45) women spontaneously complied to assess T2D. About 15% have had developed T2D and 28% prediabetes. Risk factors of T2D onset were younger gestational age at the occurrence GD, higher fasting blood glucose, and frequent use of insulin. CONCLUSIONS: Women with GD history demonstrated high risk of developing T2D. Simple changes of lifestyle were shown to be an efficient prevention protocol. Despite therapeutical education, few women spontaneously complied with T2D screening. The telephone reminders could improve the screening observance therefore patient's outcome.